2005
DOI: 10.1158/0008-5472.can-04-2076
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Generation of CD8+ and CD4+ Melanoma-Reactive T Cells by Retroviral-Mediated Transfer of a Single T-Cell Receptor

Abstract: Adoptive immunotherapy of cancer requires the generation of large numbers of tumor antigen-reactive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
97
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 30 publications
1
97
2
Order By: Relevance
“…Ex vivo T cells from the peripheral blood of healthy donors, as well as of cancer patients, can be retrovirally transduced to express a TCR to reprogram the T cell with a new specificity. [6][7][8][9][10] Although T cells engineered with a transgenic TCR have been successfully applied in cancer therapy, 11 the strategy is hampered by the fact that it requires HLA-restricted antigen presentation by the tumor, whereas many malignant cells display defects in antigen processing and HLA expression, which render them invisible to CTL responses. 2,[12][13][14] Artificially engineered chimeric antigen receptors or immunoreceptors circumvent these limitations by employing an antibody-derived binding domain that recognizes a tumor surface antigen in its natural unprocessed form, and is directly linked to the intracellular TCRz chain to provide T-cell stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Ex vivo T cells from the peripheral blood of healthy donors, as well as of cancer patients, can be retrovirally transduced to express a TCR to reprogram the T cell with a new specificity. [6][7][8][9][10] Although T cells engineered with a transgenic TCR have been successfully applied in cancer therapy, 11 the strategy is hampered by the fact that it requires HLA-restricted antigen presentation by the tumor, whereas many malignant cells display defects in antigen processing and HLA expression, which render them invisible to CTL responses. 2,[12][13][14] Artificially engineered chimeric antigen receptors or immunoreceptors circumvent these limitations by employing an antibody-derived binding domain that recognizes a tumor surface antigen in its natural unprocessed form, and is directly linked to the intracellular TCRz chain to provide T-cell stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Gene modification of T lymphocytes (23,24) may overcome the requirement for pre-existing tumor-specific immunity. We and others (25)(26)(27)(28) showed that it is possible to efficiently transduce human PBLs with retroviral vectors that encode both chains of a specific TCR, thus conferring to the transduced lymphocytes a novel antitumor specificity. In the present work, we demonstrate that primary human T lymphocytes engineered to express a murine anti-human p53 TCR can recognize both tumor lines and fresh human tumors and are able to kill p53-expressing human tumors, suggesting the potential for the direct clinical application of this approach.…”
mentioning
confidence: 99%
“…The technology of TCR gene-engineering is possibly one efficient tool with which to expand necessary specific effector T cells. Recently, retroviral vector-mediated TCR gene transduction has been utilized in basic research and some clinical trials (Roszkowski et al, 2005;Hughes et al, 2005;Morgan et al, 2006;Tsuji et al, 2005). Recently, the use of a lentiviral vector system was shown to be the optimal way to transduce specific TCR genes into naĂŻve T cells (Van Tendeloo et al, 2007).…”
Section: Discussionmentioning
confidence: 99%